PERLINDUNGAN HUKUM TERHADAP PEMEGANG HAK CIPTA DAN PEMILIK LISENSI REKAMAN BERDASARKANUNDANG- UNDANG TENTANG HAK CIPTA - Prawitri Thalib (Universitas Airlangga, 2013)
As for the types of intellectual property rights set forth in the Agreement on Trade Related Aspects of Intellectual Property Rights, Including Tradeon Counterfeit Goods(TRIPs), is Copyright, Patents, Trademarks, Geographical Indications, Integrated Circuit Layout, Secret Trade and Plant Variety Protection. Part of the Intellectual Property Rights that discussed the authors in this paper is Copyright. Copyright is the exclusive right, a right that is recognized by the world, is required to be protected by law but violations of the Copyright are happening everywhere. Proliferation of pirated goods in the form of DVD, VCD, AUDIO CD, CD/DVD Game and Cassette Tape in the market, whereas the Copyright as stipulated in Law No.19 of 2002 on Copyright, Copyright mentioned that the Creatoris the Exclusive Rightsor the Copyright holder to publish or reproduce his workor give permission for it.Keywords: copyrights, exclusive rights, counterfeit.